Iodine in Danish Groundwater and Drinking Water - Voutchkova, Denitza Dimitrova (AU Library Scholarly Publishing Services, 2018)
This dissertation is a result of a three-year PhD project which was part of the GEOCENTER research project “Iodine in the hydrological cycle of Denmark: implications for human health”, jointly financed by the Geological Survey of Denmark and Greenland (GEUS) and Aarhus University (AU). The study was conducted between August 2011 and July 2014 under the main supervision of Søren M. Kristiansen (AU) and Birgitte G. Hansen (GEUS). In my PhD dissertation, I address the following research objectives: 1) to map iodine concentration and speciation in drinking water and groundwater in Denmark, 2) to study the spatial patterns and to elucidate the factors governing them, and 3) to evaluate the importance of the spatial variation of drinking water iodine to the populations’ nutrition (health). To do this, I used two types of data: 1) from two sampling campaigns designed as part of this project (drinking water: 2013, groudnwater and drinking water: 2012), and 2) historical data extracted from the public nationwide geological and hydrological database, Jupiter. (two groudnwater datasets: 1933-2011 and 2011-2014). See the extended Abstract (PhD Dissertation) for further details on results, implications, and potential for further research. This PhD dissertation is paper-based type (not a monography) and it includes a Summary Chapter, followed by five manuscripts. Four of the manuscripts are now published in peer-reviewed journals, so those have been removed from the file. No other changes to the content of the PhD dissertation have been made post-submission to AU.